Metal chalcogenides as counter electrode materials in quantum dot sensitized solar cells: a perspective. Issue 46 (2nd November 2015) - Meng, Ke; Chen, Gang; Thampi, K. Ravindranathan
Abstract : This article reviews the application of metal chalcogenide counter electrodes in quantum dot sensitized solar cells. Abstract : The quantum dot sensitized solar cell (QDSSC), which has an analogous structure and working principle to the dye sensitized solar cell, has drawn much attention due to its characteristic advantages like ease of fabrication, robustness and the potential for multiple electron generation. Much effort to optimize various components of QDSSCs has been taken to boost the overall device performance. It is well known that the counter electrode (CE) plays a vital role in sensitized solar cells and could profoundly impact the device performance. Recently, metal chalcogenides have been explored as superb counter electrode materials for QDSSCs. This review gives a panorama of both conventional noble metals and carbon CEs and newly emerged metal chalcogenide CE materials for QDSSCs, while the influence of CE materials on the overall device performance is stressed in detail. The Conclusions and prospects emphasizes the importance of studies on metal chalcogenide CE materials and puts forward the remaining challenges that need to be addressed.